Attaining Flexible Stability by Integrating Total Quality Management and Socio-Technical Systems Theory - Manz, Charles C.; Stewart, Greg L. (Organization Science, 1997)
Total Quality Management (TQM) and Socio-technical Systems Theory (STS) are two widely recognized and used work design strategies. While both approaches advocate some degree of technical proficiency and employee involvement, little research exists that has investigated potential synergies to be gained from combining central elements of the two. This paper directly addresses how these two approaches can be combined to simultaneously achieve organizational stability and flexibility. Contradictory as well as complementary features of TQM and STS are explored. A theoretical model addressing the potential for synergistic integration of TQM and STS is developed. Research propositions derived from this model are also provided to guide future research. Research based on these propositions can be instrumental in guiding ongoing organizational investments in TQM and STS. Ultimately, an integrated approach may be established that promises to simultaneously foster efficiency, stability, innovation, flexibility, psychological ownership, quality of worklife, continuous and discontinuous learning, and high organizational performance and customer satisfaction.